Helicobacter Pylori and Sociodemographic Characteristics Distribution - Shaiban, Amenah Jamal; Nayyef, Sura Hameed (Journal for Research in Applied Sciences and Biotechnology, 2024)
Introduction and Aim: Helicobacter pylori is a gram-negative bacterium that affects up to half of the world's population, particularly in poorer nations. It is the leading cause of chronic gastritis, ulcers, gastric lymphoma, and gastric cancer, with more frequent cases in children and adolescents. Transmission can occur through fecal-oral, gastro-oral, oral-oral, or sexual means. The infection is caused by H. pylori's urease activity, invasion of host gastric epithelial cells, and adherence to host cell receptors. Early treatment can enhance gastric protection. Materials and Methods: Between November 2022 and July 2023, 103 samples were collected from patients at Mihrabani Surgical Hospital in Erbil City to identify Helicobacter pylori infection. Blood samples and stool samples were used to test for antibodies. Results: The study found a relatively equal gender representation in the patient and control groups, with 48.48% of men in the patient group and 48.64% in the control group. However, there are significant differences in age distribution, with G3 of age (<35) having the highest prevalence of H.pylori (48.48%). Additionally, 62.12% of patients are rural residents, while 97.29% of the control group are urban residents. Finally, 56.07% of patients are married, indicating a significant difference. Conclusion: The study found equal gender representation in patient and control groups but significant age differences, rural residency, and marital status, with G3 under 35 having the highest H.pylori prevalence.